2014
DOI: 10.3855/jidc.4682
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of prolonged hospital stay in children with viral severe acute respiratory infections

Abstract: Introduction: Severe acute lower respiratory infections (SARIs) are one of the major causes of morbidity and mortality in young children, especially in developing countries. The present study focused on detection of risk factors for prolonged hospital stays among children with viral SARIs. Methodology: A sentinel surveillance study was conducted at Cairo University Hospital (CUH) between February 2010 and May 2011. Nasopharyngeal (NP) and oropharyngeal (OP) swabs were collected from all children admitted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
(47 reference statements)
5
24
2
Order By: Relevance
“…The worldwide distribution of viral etiology as a cause of SARI varies between 2% and up to 78% [7,11,13,14]. In this study, we found a viral etiology in 33.5 % of hospitalized patients with SARI, which is comparable to previous studies conducted in either developing or Middle Eastern countries [9][10][11]13]. The finding that two-thirds of SARI cases had no pathogen detected suggests that poor or late specimen collection may have contributed to a lower yield of detected viruses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The worldwide distribution of viral etiology as a cause of SARI varies between 2% and up to 78% [7,11,13,14]. In this study, we found a viral etiology in 33.5 % of hospitalized patients with SARI, which is comparable to previous studies conducted in either developing or Middle Eastern countries [9][10][11]13]. The finding that two-thirds of SARI cases had no pathogen detected suggests that poor or late specimen collection may have contributed to a lower yield of detected viruses.…”
Section: Discussionsupporting
confidence: 86%
“…The 2009 influenza pandemic had highlighted the need for more global data on severe influenza disease, so the WHO recommended conducting surveillance for hospitalized severe acute respiratory infection (SARI), as well as influenza-like illness (ILI) in outpatients [3][4][5][6]. SARI surveillances are now conducted in many countries around the world; however, because of limited resources, they are only conducted in limited settings in the Middle East and Egypt [7][8][9]. Furthermore, the role of individual viral or atypical bacterial infection in causing ARI is not usually documented [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The inter‐rater agreement for study selection was high ( κ = 0.81). Finally, 66 full texts including 67 studies were included (one paper included two studies) …”
Section: Resultsmentioning
confidence: 99%
“…In the same manner, in a prospective cohort study that included 232 indigenous infants hospitalized with bronchiolitis, McCallum et al 18 identified a 12-point severity score (including accessory muscle use) as the only factor associated with prolonged LOS. The presence of cyanosis was significantly associated with prolonged LOS in a population of 1046 children hospitalized for acute lower respiratory infections in a hospital located in Cairo, Egypt 32. Janahi et al 28 in a retrospective cohort study examined an inpatient population of 369 infants admitted with acute bronchiolitis in a hospital in Qatar, and found that retraction was an independent predictor of longer LOS.…”
Section: Discussionmentioning
confidence: 99%